The role of serum tenascin-c and procalcitonin in predicting the severity of acute pancreatitis - Adil Ugur Cetin; Fatih Kamis; Ece Unal Cetin; Mehmet Arslan; Yavuz Beyazit (Medicine Science, 2021)
Acute pancreatitis (AP) constitutes an activation of a variety of enzymes secreted by the pancreas and is a continuing inflammatory process where the pancreas damages itself. Although a variety of factors reported to have an association with disease severity, the role of Tenascin-C and procalcitonin in the pathophsiology of the disease has not been clearly elucidated yet. Therefore, this study aimed to assess whether tenascin-C and procalcitonin would be useful in predicting disease severity and prolonged hospital stay in conjunction with several prognostic scoring systems. A total of 44 AP patients (male/female: 24/20), and 40 healthy subjects (male/female: 20/20) were enrolled in this study. Tenascin-C and procalcitonin levels with other markers of inflammation were measured for all study participants. Prognostic scoring systems were used as to predict the disease severity in AP patients. Serum tenascin-C levels was higher in AP patients at onset of the disease compared with healthy controls. There were statistically significant and positive differences identified between serum Tenascin-C with Atlanta (p=0.000 r=0.538), Ranson (p=0.041 r=0.310) and Imrie (p=0.039 r=0.312) scoring systems. There was a statistically significant and positive correlation between CRP with serum tenascin-C (p=0.015 r=0,366) levels. Serum tenascin-C levels had high sensitivity (76.5%) and specificity (77.8%) for prediction of severe pancreatitis according to the Atlanta scoring system (AUC:0.809). The present study demonstrated that tenascin-C and procalcition levels are elevated in AP. Moreover, the appraisal of tenascin-C levels in patients with AP in conjunction with other markers of inflammation may provide additional information in estimating AP severity. [Med-Science 2021; 10(2.000): 493-7]